Experimental Investigation of Thermal-Mixing Phenomena of a Coaxial Jet with Cylindrical Obstacles - Kok, Besir; Varol, Yasin; Ayhan, Huseyin; Öztop, Hakan Fehmi; Demiryurek, Sifa G. (Amer Inst Aeronautics Astronautics, 2018)
In this study, the thermal-mixing phenomenon of a coaxial jet with cylindrical obstacles is analyzed experimentally. Cylindrical obstacles are located in front of the coaxial jet to control the thermal-mixing behavior. A coaxial-jet nozzle designed and inserted into a rectangular cross section confined channel. The coaxial jet consists of two water jets at different temperatures that were positioned on the same axis. An experimental setup was constructed to perform two different obstacle combinations and the standard case having no obstacles. These three cases were performed with six different boundary conditions. Also, a comparison of experimental results with available numerical results shows a good agreement. The obtained results indicate that the mixing performance of cold and hot fluids is a function of temperature difference, and it increases as the temperature difference between jets increases. Inserting obstacles has significant effects on the mixing performance, and these effects of obstacle change with increasing temperature difference between cold and hot jets. Locating various combinations of obstacles in the mixing channel does not affect the dominant frequency that is found as 5 Hz. On the other hand, using cylindrical obstacles may change the magnitude of thermal fluctuations after them. Consequently, this study exposed that the chosen parameters have remarkable effects on the mixing behavior of the coaxial jet, and these parameters can be used to control the mixing phenomenon.
Keywords: Flow